Comparison of Idiopathic Interstitial Pneumonias with Their Connective Tissue Disease-Associated Counterparts - F. Moore, Charles; L. Perez, Rafael (Current Respiratory Medicine Reviews, 2015)
Interstitial lung disease (ILD) has been described as a potential clinical finding in essentially all of the connective tissue diseases (CTD). Patients with Rheumatoid Arthritis most commonly develop a fibrotic pattern consistent with Usual Interstitial Pneumonia while Non-Specific Interstitial Pneumonia is more commonly seen in the remainder of the collagen vascular diseases, in particular in patients with Scleroderma-spectrum disease. The etiology of ILD in the CTDs is poorly understood and the progression of lung disease may not correlate with the more typical autoimmune manifestations. Therapy of CTD-associated ILD remains unsatisfactory and the clinical picture may be clouded by the probability that some patients with apparently idiopathic ILD will, eventually, evolve into a more clearly-defined CTD and by the possibility that in some patients with lung-dominant disease subtle evidence of underlying CTD may be missed. In this review we will examine the etiologic, histologic, radiographic, and epidemiologic features of the Idiopathic Intersitial Pneumonias in comparison with their CTD-associated counterparts as well as address some of the difficulties in assessing whether ILD is truly idiopathic or instead part of an underlying autoimmune process.
Keywords: systemic sclerosis